ปัจจัยที่มีผลต่อการใช้บริการสินเชื่อจุลภาคของธนาคารอิสลามแห่งประเทศไทยในจังหวัดปัตตานี - หะยีสะอิ, อับดุลเลาะ (Al-HIKMAH Journal, 2021)
Abstract The aimed of this research to study the factors that affected the use of Islamic Microfinance in Islamic Bank of Thailand service in Pattani province. By studied five key factors which consisted of 1) Outreach Client 2) product service 3) credit mechanism 4) Human resource and 5) location factors. The research was conducted using qualitative analysis by collecting secondary data from the primary data from 12 in-depth interviews, the Director Islamic Microfinance, Manager Pattani center, Deputy manager Pattani center, Senior officer, Bank Coordinator and customer. By through non-participating observations Data analysis by presenting the data to be analyzed and summarized and presented by descriptive analysis method. The research results showed that all 5 of the above factors Able to meet the needs of micro-level customers in Pattani Province is a satisfied page. This can be observed from the number of money and the number of customers using the credit services in all eight projects that Islamic Bank has provided, although the micro-credit operation in Pattani Province. There will be some problems and obstacles, but it will not affect the operation much Keywords: Islamic Microfinance, Islamic bank of Thailand, Factors, Service use